Impact of Percutaneous Nephrostomy on the Efficacy of in Situ Shock Wave Lithotripsy for Upper Ureteral Stones - Yang, Seung Woo; Lee, Ji Yong; Shin, Ju Hyun; Lim, Jae Sung; Song, Ki Hak (Urology Journal, 2021)
Purpose: To investigate whether a Percutaneous nephrostomy (PCN) has any impact on the success rate of shock wave lithotripsy (SWL) and to estimate the probability of stone-free in SWL patients with upper ureter stones. Materials and Methods: Overall, 236 patients who underwent SWL for upper ureter stones between 2015 and 2019 were evaluated. Forty-nine patients who underwent PCN during SWL were identified. Medical data of the patients were retrospectively reviewed, and possible prognostic features were evaluated. Results: Out of all patients, 147 patients were selected through propensity score matching. There were no significant differences between the PCN and no PCN groups, except for a lower stone-free rate (55.1% vs. 74.5%, p = .018) and one-session success rate (24.5% vs. 50.0%, p = .003) in the PCN group. In univariate analysis, a younger age, the female sex, a smaller size of stone, lower mean stone density (MSD), and absence of PCN were positive predictive factors of being stone-free in patients who underwent SWL. In multivariate analysis, a smaller size, lower MSD, and absence of PCN were positive predictive factors of being stone-free in patients who underwent SWL. Conclusion: Stone size, MSD, and PCN were prognostic factors that influence the outcome of SWL. The presence of PCN during SWL is associated with adverse success rates in patients with upper ureter stones.